Bleomycin-Induced Neonatal Lung Injury Requires the Autocrine Pulmonary Angiotensin System - Abdelwahab, Abdellatif (Jacobs J Pulmonol, 2016)
BACKGROUND: Previous work from this laboratory demonstrated that apoptosis is regulated by a local angiotensin (ANG) system in alveolar epithelial cells (AECs). Autocrine generation of angiotensin II (ANGII) in response to endogenous or xenobiotic inducers is required for apoptosis in adult rat AECs and in AEC-derived human lung carcinoma cell line A549. Therefore, we hypothesized that a similar mechanism might also be involved in bleomycin (Bleo)-induced murine neonatal lung injury. METHODS: To investigate the local production of angiotensinogen (AGT) and ANGII in neonatal lung injury, lung explants were obtained from C57/BL6 wild type neonatal mice and were treated with Bleo in the presence or absence of an angiotensin converting enzyme (ACE) inhibitor. AGT protein, ANGII levels and caspase-9 were then measured. RESULTS: Exposure to Bleo significantly induced AGT protein (p<0.02), extracellular ANGII levels (p< 0.005) and the active form of caspase-9 (p<0.05) in neonatal lung tissue. Further, Bleo inducetion of both AGT protein and of caspase-9 were prevented by the ACE inhibitor lisinopril. CONCLUSION: These data clearly demonstrate the synthesis of AGT and ANGII in the lungs of neonates in response to Bleo. Furthermore, they suggest that manipulation of the angiotensin system may hold therapeutic potential for neonatal lung injury.